Multi-objective model for simultaneous distribution networks reconfiguration and allocation of D-STATCOM under uncertainties of RESs. Issue 1 (31st December 2022) - Safari, Amin; Karimi, Masoumeh; Hosseinpour Najmi, Parisa; Farrokhifar, Meisam
Abstract : This paper proposes an approach for simultaneous placement of distribution static compensator (D-STATCOM) and renewable energy sources (RESs) and distribution system reconfiguration (DSR) based on stochastic multi-objective modelling. Associated uncertainties of RESs in generating power, market price errors and load forecasting are modelled in this problem. The problem is optimised by non-dominated sorting genetic algorithms-II (NSGA-II) and then the best compromise solution is specified with fuzzy set theory. The aim of optimisation is to minimise installation and operation costs of distributed generation (DG) units, cost of D-STATCOM installation, the cost of procured energy from the transmission grid, costs of reactive and active power losses, line upgrade cost and DSR expense. A risk-based model of energy not supplied (ENS) as a reliability index is considered in the objective function to improve the reliability of the system. The proposed approach is validated on the IEEE 33-bus test grid.